2013
DOI: 10.1155/2013/861893
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity Improves Verbal and Spatial Memory in Older Adults with Probable Mild Cognitive Impairment: A 6-Month Randomized Controlled Trial

Abstract: We report secondary findings from a randomized controlled trial on the effects of exercise on memory in older adults with probable MCI. We randomized 86 women aged 70–80 years with subjective memory complaints into one of three groups: resistance training, aerobic training, or balance and tone (control). All participants exercised twice per week for six months. We measured verbal memory and learning using the Rey Auditory Verbal Learning Test (RAVLT) and spatial memory using a computerized test, before and aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
157
1
7

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 721 publications
(174 citation statements)
references
References 33 publications
9
157
1
7
Order By: Relevance
“…The observed effects on ADAS-Cog aligns with our previous study, 29 which demonstrated that 6 months of progressive aerobic exercise significantly improved memory (both verbal and spatial), but not EF, in women with probable mild cognitive impairment aged 70-80 years. Memory is a key cognitive domain assessed by ADAS-Cog and has been shown to be particularly impaired in persons with small subcortical strokes.…”
Section: Variablesupporting
confidence: 90%
“…The observed effects on ADAS-Cog aligns with our previous study, 29 which demonstrated that 6 months of progressive aerobic exercise significantly improved memory (both verbal and spatial), but not EF, in women with probable mild cognitive impairment aged 70-80 years. Memory is a key cognitive domain assessed by ADAS-Cog and has been shown to be particularly impaired in persons with small subcortical strokes.…”
Section: Variablesupporting
confidence: 90%
“…There have also been exercise-instigated improvements reported in other studies involving adults who are at risk of AD [85]. Furthermore, one intriguing study suggests speci c types of physical activity can differentially affect individual facets of memory; in MCI patients, verbal memory was improved by aerobic exercise, but spatial memory was improved by both aerobic and resistance training [84].…”
Section: Exercisementioning
confidence: 90%
“…This restoration of neurogenesis occurred once the AD-like symptoms were underway, revealing a potential for not only a delay of the symptoms, but actually a reversal. In a study of mild cognitive impairment (MCI) patients [84], those in the control condition found their declarative memory deteriorated after six months, as the course of the disease progressed. Strikingly, however, those in the exercise conditions had memory which was not only preserved after six months, but actually improved compared to baseline.…”
Section: Exercisementioning
confidence: 99%
“…Age-related deficits in the central nervous system control [5], physiological and biomechanical changes within the muscular system [6], and functional impairment of sensory organs [7] disrupt walking mechanics and movements of individual body parts in relation to each other (e.g. [2,8]).…”
Section: Introductionmentioning
confidence: 99%